Strategies for improving minor irrigation systems in Sri Lanka - Groenfeldt, D.J.; Alwis, J.; Perera, J. (International Water Management Institute, 1988)
Proceedings of a Workshop sponsored jointly by ARTI and IIMI, 11-12 December 1987.